How do you solve the following function question?

User Generated

zfzvgu@fnvagznexfpub

Mathematics

Description

If f(1) = 3 and f(n) = -2f(n-1) + 1 then f(5) will equal what

User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

Explanation & Answer

Thank you for the opportunity to help you with your question!

From f(n) = -2f(n-1) + 1 you get that f(2)=-2f(1) + 1=-2*3+1=-5

f(3)=-2f(2) + 1=-2*(-5)+1=11

f(4)=-2f(3) + 1=-2*11+1=-21

And Finally f(5)=-2f(4) + 1=-2*(-21)+1=43

f(5)=43

Please let me know if you need any clarification. I'm always happy to answer your questions.


Anonymous
Just what I needed…Fantastic!

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4